A comparative study on biochemical methane potential of algal substrates: Implications of biomass pre-treatment and product extraction. (June 2017) - Ansari, Faiz Ahmad; Wahal, Shantanu; Gupta, Sanjay Kumar; Rawat, Ismail; Bux, Faizal
Highlights: Four different pretreated microalgae biomass were used for biomethane production. CH4 production was nearly 2.5 times higher in lipid and protein extracted algae. Among all, LEA biomass was most suitable substrate for biomethane production. Cumulative CH4 production was higher in pretreated whole algae samples. Abstract: Dried powdered algae (SDPA), heat treated algae (MHTA), lipid extracted algae (LEA) and protein extracted algae (PEA) were digested to determine biomethane potential. The average CH4 production rate was ∼2.5-times higher for protein and lipid extracted algae than for whole algae (SDPA and MHTA) whilst the cumulative CH4 production was higher for pre-treated algae. Highest cumulative CH4 production (318.7 ml CH4  g −1  VS) was observed for MHTA followed by SDPA (307.4 ml CH4  g −1  VS). CH4 /CO2 ratios of 1.5 and 0.7 were observed for MHTA and LEA respectively. Pre-treatment processes disrupted the algal cell wall, exposing intracellular material which remained intact as opposed to product extraction processes which broke down the intracellular compounds resulting in changes in elemental composition and decreases the cumulative gas yield and CH4 /CO2 ratio. Comparative analysis determined that the most profitable route of biomass utilisation was protein extraction followed by biogas production giving ∼2.5-times higher return on investment.